ANALISIS PENGGUNAAN CASHLESS (E-WALLET) SEBAGAI SARANA UNTUK MEMUTUS PERKEMBANGAN VIRUS (TINJAUAN ASPEK PEMASARAN KELAYAKAN BISNIS) - M. Bahtiar Saputra; Anak Agung Elik Astari; Ni Luh Indiani (Nusantara Hasana Journal, 2022)
Indonesian people are starting to get used to cashless payments. Cashless payments became popular in Indonesia in 2014, since Bank Indonesia started the National Non-Cash Movement (GNNT), which was the first step towards realizing a cashless payment society. This research was conducted with the aim of knowing the analysis of the use of cashless (e-wallet) as a means to determine the development of the virus (a review of the marketing aspects of business feasibility). This type of research is a qualitative descriptive research – quantitative research method with observation and documentation techniques. The subject and object of this research is SME trap (Jejak Bali Culinary) with purposive sampling technique. The results of this study are the main function of OVO merchants is an application intended for merchant owners who collaborate with OVO to help manage financial transactions both in terms of income and expenses. Based on competitor analysis, Go-Pay is a digital payment that has the potential to compete with OVO’s presence among consumers. e - money users. based on a SWOT analysis of strengths, weaknesses, opportunities, and threats in the use of OVO merchants in business opportunities in the culinary field at JEBAK (Jejak Bali Kuliner) that the use of the OVO merchant application is in a strong position  and able to continue to grow in market share. The existence of OVO can be used as a forum to seize very profitable business opportunities for businessmen. The opportunities that can be exploited by businessmen when using the OVO merchant application are to simplify the payment system with consumers, payments have been provided through an expedition machine that is easy to use, can streamline time, is flexible, is safe, reduces production costs and helps merchant financial management.  Factor analysis, promotions and cashback from OVO companies are opportunities that are used by business people to increase the number of buyers and the amount of income through the provision of bonuses from each transaction that takes place.